Faktor yang Mendukung Kelengkapan Pengisian Buku KIA (Kesehatan Ibu dan Anak) - Ustriyaningsih Ustriyaningsih (Universitas Malahayati Lampung, 2023)
ABSTRACT The KIA Handbook is a manual that contains information sheets and records of health services for mothers and children. However, the use of the KIA handbook has not achieved maximum results because the documentation system is still done conventionally. This study aims to analyze and describe the input, planning, and organizing factors that affect the completeness of filling out the KIA handbook. This study uses a literature review method. Journal searches were obtained from the Google Scholar database using keywords and inclusion criteria. The steps of data analysis are: data collection, data reduction, data presentation, and conclusions. The article search results obtained 34 articles published in national online journals using the Google Scholar search engine with keywords and inclusion criteria, namely: time period, language, subject, type of article, and theme of article content. The conclusions in this study are: (1) The input factors that affect the completeness of filling out the KIA book from the midwife's side are knowledge, attitudes, skills, while from the mother's side, namely in terms of knowledge, (2) Planning factors that affect the completeness of filling out the KIA book are service SOPs. Antenatal care at the Public Health Center is made by the Public Health Center based on the integrated antenatal service guidelines set by the District Health Office, and (3) Organizing factors that affect the completeness of filling out the KIA handbook, namely cooperation and joint commitment by each part involved such as: Health Office, Head of Public Health Center, Implementing Midwives, Local Government (Districts), Pregnant Women's Families, and Employers Keywords: KIA Handbook (Maternal and Child Health), Input, Planning, Organizing, Supporting Factors ABSTRAK Buku Panduan KIA merupakan buku pedoman yang berisi lembar informasi dan catatan pelayanan kesehatan ibu dan anak. Namun penggunaan buku pedoman KIA belum mencapai hasil yang maksimal karena sistem pendokumentasiannya masih dilakukan secara konvensional. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan faktor-faktor input, perencanaan, dan pengorganisasian yang mempengaruhi kelengkapan pengisian buku pedoman KIA. Penelitian ini menggunakan metode literature review. Pencarian jurnal diperoleh dari database Google Scholar menggunakan kata kunci dan kriteria inklusi. Langkah-langkah analisis data adalah: pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil pencarian artikel diperoleh 34 artikel yang dimuat di jurnal online nasional menggunakan mesin pencari Google Scholar dengan kata kunci dan kriteria inklusi yaitu: jangka waktu, bahasa, subjek, jenis artikel, dan tema isi artikel. Kesimpulan dalam penelitian ini adalah: (1) Faktor input yang mempengaruhi kelengkapan pengisian buku KIA dari sisi bidan adalah pengetahuan, sikap, keterampilan, sedangkan dari sisi ibu yaitu dari segi pengetahuan, (2) Perencanaan faktor yang mempengaruhi kelengkapan pengisian buku KIA adalah SOP pelayanan. Asuhan antenatal di Puskesmas dilakukan oleh Puskesmas berdasarkan pedoman pelayanan antenatal terpadu yang ditetapkan oleh Dinas Kesehatan Kabupaten, dan (3) Mengorganisir faktor-faktor yang mempengaruhi kelengkapan pengisian buku KIA yaitu kerjasama dan komitmen bersama oleh masing-masing bagian yang terlibat seperti: Dinas Kesehatan, Kepala Puskesmas, Bidan Pelaksana, Pemerintah Daerah (Kabupaten), Keluarga Ibu Hamil, dan Pemberi Kerja Kata Kunci: Buku KIA (Kesehatan Ibu dan Anak), Input, Perencanaan, Pengorganisasian, Faktor Pendukung